Clinical characteristics and prognosis of breast cancer patients with ovarian metastases - Gao, Chunyan; Li, Yan; Ma, Xiaoping; Zhao, Zhenhui; Li, Li; Liu, Dan; Li, Bingyu; Zhao, Bing (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the clinical characteristics, overall survival (OS), and prognostic factors associated with breast cancer patients who have ovarian metastasis (OM).Materials & methodsThis retrospective single-center study analyzed 41 breast cancer patients with pathologically confirmed OM who underwent bilateral oophorectomy between 2011 and 2022. Data on clinical-pathological characteristics, molecular subtypes, detection methods, and survival were collected. The survival times were analyzed using Kaplan-Meier survival analysis. Prognostic factors were assessed through Cox regression models.ResultsThe cohort consisted of 33 (80.5%) invasive ductal carcinoma (IDC) and 8 (19.5%) invasive lobular carcinoma (ILC) cases. Most patients (87.8%) were hormone receptor-positive. Patients with ILC were significantly older at initial diagnosis than IDC patients (median 45 vs. 37 years, P = 0.014). OM was detected earlier in IDC, often incidentally during ablation surgery (54.5% vs. 12.5% for ILC, P = 0.032), whereas ILC patients typically presented with symptoms. For the entire cohort, the median OS was 85.0 months, while the median OS after OM was 28 months. Notably, patients with ILC exhibited a significantly shorter OS after OM (11.5 months) compared to those with IDC (30 months; P = 0.01). Furthermore, the interval from the initial diagnosis of breast cancer to the emergence of OM was significantly associated with the OS of these patients (P < 0.05), serving as an independent prognostic indicator.ConclusionsOM, which may not exhibit overt clinical manifestations in the early stage, significantly affects the survival of BC patients. The ILC histological type is associated with a particularly unfavorable post-OM prognosis, and the interval from initial diagnosis to OM is a key prognostic indicator. These findings may guide clinical management in these patients.